A New Technique for New York Stock Exchange (NYSE) Data Analysis Using Apache Pig - Halder, Sayantan; Dugar, Dristi; Nath, Ira; Rakshit, Pranati; Singh, Dharmpal (International Journal of Computer Sciences and Engineering, 2020)
In the given project entitled NYSE Data Analysis using Big Data (Apache Pig), a database of New York Stock Exchange collected from the open source of New York Stock Exchange daily report where we will analyse the data and produce the required output. Here, the data is referred to the daily stocks of all the companies or industries which is enlisted in the NYSE daily report. We will use the Apache Pig which is used to analyse large data sets representing them as data flows. It is designed to provide an abstraction over MapReduce, reducing the complexities of writing a MapReduce program. Basically, the MapReduce uses java program to execute and to analyse the dataset and it has to use certain logics to provide the desired output. Apache Pig gives us a better platform to do the work more efficiently and quickly using certain logical lines. Apache Pig is one of the best platforms for the analyzation of Big Data